The Microenvironment in Barrett’s Esophagus Tissue Is Characterized by High FOXP3 and RALDH2 Levels - Lind, Alexandra; Siersema, Peter D.; Kusters, Johannes G.; Konijn, Tanja; Mebius, Reina E.; Koenderman, Leo (Frontiers in Immunology, 2018)
Metaplasia in Barrett’s Esophagus (BE) is characterized by the transition of squamous epithelium into intestinal-type columnar epithelium. The immune response in BE shares many similarities with the response found in the gut, which is different from the response found in a normal-looking esophagus. Here we investigated the role of the genes associated with the retinoic acid (RA) pathway in BE, as RA is important not only in shaping the gut’s immune response, but also in the induction of metaplasia in vitro. mRNA was isolated from esophageal and duodenal biopsies from BE (n=14), reflux esophagitis (RE) patients (n=9) and controls (n=12). cDNA was made and qPCR was performed. The expression of RALDH1, CYP26A1, MAdCAM1 were similar for both the BE and duodenum, but different when compared to squamous esophageal epithelium. BE was characterized by a higher expression of RALDH2 and FOXP3, compared to the duodenum. In BE, RALDH2 correlated with expression of the mDC-specific genes: CD11c and CD1c. Also, RALDH2 expression correlated with RAR-β and FOXP3. Hierarchical clustering on the expression of multiple relevant genes demonstrated that BE, duodenum and SQ tissues are clustered as three different groups. The differential expression of RA-specific genes and DC-subsets indicates that BE resembles duodenal tissue. The higher expression of RALDH2 and FOXP3 in BE points at a mechanism associated with a possible anti-inflammatory microenvironment. This aberrant immune regulation might contribute to the altered tissue and immune responses found in BE.